2018
DOI: 10.1111/pde.13545
|View full text |Cite
|
Sign up to set email alerts
|

Self‐initiated use of topical cannabidiol oil for epidermolysis bullosa

Abstract: Epidermolysis bullosa is a rare blistering skin disorder that is challenging to manage because skin fragility and repeated wound healing cause itching, pain, limited mobility, and recurrent infections. Cannabidiol, an active cannabinoid found in cannabis, is postulated to have antiinflammatory and analgesic effects. We report 3 cases of self-initiated topical cannabidiol use in patients with epidermolysis bullosa in an observational study. One patient was weaned completely off oral opioid analgesics. All 3 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 14 publications
2
78
0
1
Order By: Relevance
“…A particularly interesting, although anecdotal, result has recently been published by Chelliah et al, who described the benefits that CBD provided as anti-inflammatory agent in three patients affected by epidermiolysis bullosa. Paediatric patients benefited from the use of topical CBD (applied as an oil, cream and spray by their parents) leading to a reduction in pain and blistering as well as rapid wound healing [ 100 ]. There were no adverse effects reported, either by the patients or their families, of this topical use of CBD.…”
Section: Current Drug Dosage Forms and Novel Delivery Systemsmentioning
confidence: 99%
“…A particularly interesting, although anecdotal, result has recently been published by Chelliah et al, who described the benefits that CBD provided as anti-inflammatory agent in three patients affected by epidermiolysis bullosa. Paediatric patients benefited from the use of topical CBD (applied as an oil, cream and spray by their parents) leading to a reduction in pain and blistering as well as rapid wound healing [ 100 ]. There were no adverse effects reported, either by the patients or their families, of this topical use of CBD.…”
Section: Current Drug Dosage Forms and Novel Delivery Systemsmentioning
confidence: 99%
“…Regarding the clinical efficiency of cannabinoids in human skin fibrotic diseases, only scarce evidence is available. A short literature report including three patients exhibiting epidermolysis bullosa described faster wound healing following the selfadministration of cannabidiol (CBD) 34 . Recently, a small clinical study described a beneficial effect of topical cannabidiol in acne scars 35 .…”
mentioning
confidence: 99%
“…Indeed, one patient was weaned completely off oral opioid analgesics, and all 3 patients reported faster wound healing, less blistering, and amelioration of pain. The authors concluded that the effects might have been due to the anti-inflammatory activity of CBD, but in light of the above data, one can speculate that CBD might have beneficially modulated the keratin expression profile as well [183]. Likewise, in another small pilot study, three EB patients, who were prescribed pharmaceutical-grade sublingually administered cannabinoid-based medicine (CBM) comprising THC and CBD, reported improved pain scores, reduced pruritus and decreased overall analgesic drug intake [184].…”
Section: Translational Potential Of the Cutaneous Cannabinoid Signmentioning
confidence: 99%